Techno-Functional Properties of Burgers Fortified by Wild Garlic Extract: A Reconsideration - Vladimir S. Kurćubić; Slaviša B. Stajić; Nemanja M. Miletić; Marko M. Petković; Marko P. Dmitrić; Vesna M. Đurović; Volker Heinz; Igor B. Tomasevic (Foods, 2023)
The aim of this research was to examine the chemical properties of freshly squeezed wild garlic extract (FSWGE) and its use as an additive in burgers (BU). Technological and sensory properties of such fortified burgers (BU) were determined. LC-MS/MS analyses identified thirty-eight volatile BAC. Allicin prevalence (11.375 mg/mL) is the key parameter determining the amount of FSWGE added in raw BU (PS-I 1.32 mL/kg, PS-II 4.40 mL/kg, and PS-III 8.79 mL/kg). Minimum inhibitory concentrations (MIC) and minimum bactericidal concentration (MBC) values of the FSWGE and evaporated FSWGE (EWGE) were determined against the six microorganisms using a microdilution method. The data indicated that using FSWGE can result in a reduced risk of Serratia marcescens (MIC = 50 mg/mL; MBC = 60 mg/mL), Listeria monocytogenes (MIC = MBC = 90 mg/mL), Escherichia coli and Staphylococcus aureus (MIC = 90 mg/mL; MBC ≥ 100 mg/mL), and Salmonella enteritidis and Enterococcus faecium (MIC = 100 mg/mL; MBC > 100 mg/mL) in BU. Changes in antioxidant (AOX) capacity were followed during cold storage (up to 10 days) and freezing (90 days). It was shown that PS-III had the highest level of AOX capacity during the entire period of cold storage, revealing 8.79 mL FSWGE/kg BU as the most suitable effective concentration. Adding FSWGE did not negatively affect the technological and physico-chemical properties during both cold and freeze storage. Regarding sensory evaluation, modified BU received mostly higher scores compared to control. The results of this study have demonstrated the great potential of wild garlic extract usage in the creation of safe products with prolonged shelf life.